A multi-objective model for inventory and planned production reassignment to committed orders with homogeneity requirements. (October 2018) - Esteso, Ana; Alemany, M.M.E.; Ortiz, Ángel; Peidro, David
Highlights: Production lots in certain companies are non-homogeneous. Customers require homogeneity among units of the same and different products. Discrepancies in planned and real homogeneous sublots can preclude orders deliveries. A MOILP model to reallocate products to orders in shortage situations is proposed. Model validation and experimental design provide managerial insights. Abstract: Certain industries are characterized by obtaining non-homogeneous units of the same product. However, customers require homogeneity in some attributes between units of the same and different products requesting in their orders. To commit such orders, an estimation of the homogeneous product to be obtained can be used. Unfortunately, estimations of homogenous product quantities can differ considerably from real distributions. This fact could entail the impossibility of accomplishing the delivery of customer orders in the terms previously committed. To solve this, we propose a multi-objective mathematical programming model to reallocate already available homogeneous products in stock and planned production to committed orders. The main contributions of this model are the consideration of the homogeneity requirement between units of different lines of the same order, the allowance of partial deliveries of order lines, and the specification of some relevant attributes of products to accomplish with the customer homogeneity requirement. Different hypotheses are proved through experiments and statistical analyses applied to a ceramic tile company. The ε-constraint method is used to obtain an implementable solution for the company. The weighted sum method is used when proving other hypotheses that offer some managerial insights to companies.